The Determination of Bronchopneumonia Diagnostic Codes in Patients of The National Health Insurance - Lathifina, Yashna Meutia; Kristina, Indah; Rahmi, Junaida; Sucipto, Sucipto (Edu Masda Journal, 2023)
Coding is the activity of providing the diagnosis in accordance with International Statistical Classification of Diseases and Related Health Problems as well as providing a procedure code in accordance. Accuracy in coding a disease and action is very important because it is related to health service financing because it determines the smoothness and process of submitting claims for reimbursement of health service costs to BPJS. The purpose of this study was to identify the code code coded by the coder in the codefication of bronchopneumonia cases in National Health Insurance patients by reviewing the coding procedures carried out by the coder. This research uses a descriptive method with a quantitative approach. In collecting data, researchers use observation. The results showed that the accuracy of codefication in bronchopneumonia patients was eighty-two point thirty-five percent in fifty-six medical records of precise diagnosis and seventeen point sixty-five percent in forty-two medical records of improper diagnosis. The accuracy of the bronchopneumonia code as the primary diagnosis Totaled to ninety point forty-eight percent of the exact code and nine point fifty-two percent of the improper code of the forty-two medical records. The code of bronchopneumonia as a secondary diagnosis Totals to sixty-nine point twenty-three percent of the exact code and thirty-point seventy-seven improper codes of twenty-six medical records. It is recommended that there is a need to increase the accuracy of the coder in reading the diagnosis written by the doctor on the medical resume as well as the consistency.